High-compliance work systems: Innovative solutions for firm success and control of foreign corruption - Posthuma, Richard A. (Business horizons, 2022)
Enforcement of laws that prevent corrupt international business dealings has recently intensified. Firms have paid record-setting fines of hundreds of millions of dollars, and individuals have been tried and convicted. This escalating situation demands effective action from business leaders. Compliance has become increasingly complicated as more countries have enacted antibribery laws. To address this situation, I identify four root causes of corruption and present innovative real-world examples of solutions. Combinations of these solutions can be crafted to create high-compliance work systems (HCWSs) to avoid corruption. Firms can formulate their own unique, innovative, and dynamic models to achieve high levels of firm success while also avoiding corruption. These models go beyond trade-off thinking, which suggests that compliance must be exchanged for performance. Pivoting away from such trade-off thinking enables innovative solutions to manage corruption risks and offers firms a sustained competitive advantage over their peers.